Identificacion de Acidovorax avenae citrulli en semillas de sandia en Nicaragua - Muñoz, M.=700 1 Monterroso, M.
(Es)
ilus., 1 ref.
Keywords: MANCHAS; MELON; SANDIA; ACIDOVORAX AVENAE; MANCHA BACTERIAL DEL FRUTO